The Asymmetric Impact of COVID-19 Pandemic on the Crude Oil-stock Markets Nexus in KSA: Evidence from a NARDL Model - Gheraia, Zouheyr (International Journal of Energy Economics and Policy, 2022)
This paper estimates the asymmetric relationship between the crude oil market, stock market and COVID-19 pandemic in the case of KSA during the period of 15/03/2020 to 03/02/2021. Nonlinear and long-run asymmetric cointegration were utilized for comprehensive research on this topic. Our findings are as follows: positive and negative shocks to the COVID-19 pandemic reduce stock market. Moreover, positive shock to crude oil market increases stock market, but negative shock has a negative and insignificant effect. Based on the results, this study concludes with suitable policy prescription.